Status Perkembangan Perbaikan Sifat Genetik Padi Menggunakan Transformasi Agrobacterium - Rahmawati, Syamsidah (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2006)
Genetic transformation of rice becomes an important research area in recent years. Rice is staple food for almost half of world population and has been extensively used as a plant model system for monocotyledonous plant. Compare to direct DNA transfer techniques (PEG, electroporation, and DNA bombardment), Agrobacterium tumefaciens-mediated transformation was considered to be more advantageous because it is easy to handle, integration and segregation pattern are more predictable, and the likelihood to get transgenic plant with low copy number is high, thus decreasing gene silencing phenomena. Various important genes have been introduced into rice genome via Agrobacterium transformation. A number of important factors affecting theÂ Agrobacterium transformation and the application of this technique in the next future will be discussed.